VOCATIVE IN TEACHING CROATIAN AS A SECOND LANGUAGE (Philological Studies, 2022)
In the teaching of Croatian as a second language, the vocative is usually introduced as the final, seventh case. This is due to its specific morphological, syntactic, and semantic-pragmatic characteristics, but it is also because it is used the least. It is specific because it is an independent case (the same as the nominative), has a pronounced communicative function (addressing, invoking), and is only partially grammaticalized. Indeed, nominative and vocative morphological features are often equated as a result of the interaction of foreign language contacts, organic idioms, and different functional styles. It is sometimes said that the vocative is extinct, but it is more accurate to say that it is demorphologized. The vocative is not implemented consistently like in other cases, which poses a challenge in teaching Croatian as a second language. The paper considers the teaching of the vocative while respecting the communication needs of students of Croatian as a second language at the beginning level (A2 level according to the Common European Framework of Reference for Languages) as well as the situation in modern Croatian.